Electric vehicle charging stations load impact on the distribution network - Talal Guia; Benalia M’Hamdi; Ali Khechekhouche (The Journal of Engineering and Exact Sciences)
Integrating large numbers of electric vehicles will lead to operational and planning difficulties for distribution networks. The installation of electric vehicle charging stations (EVCS) increases power losses, affects stability, and degrades the reliability of the distribution network, resulting in dissatisfaction among customers. This work describes the impacts of the integration of electric vehicle charging stations on power losses, voltage stability index, and the main  reliability indices as a function of the position and size of electric vehicle charging stations. This investigation was carried out on the IEEE 33 bus test system. According to the results, a high concentration of EVs increases peak demand, leading to greater energy losses, adversely affecting stability, and degrading reliability indices of the distribution network. The choice of installation points for EVCS is therefore very important, as some points induce greater energy losses than others and affect stability and reliability more than others. Measures to mitigate the effects of EVCS installation on distribution networks are crucial.